2014
DOI: 10.29244/cb.1.2.83-88
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Wungu Leaf (<i>Graptophyllum pictum</i> (L) Griff) Extract in Reducing Blood Glucose Level of Hyperglycemic Mice

Abstract: Wungu leaf (Graptophyllum pictum (L.) Griff) is a plant thought to have potential use in alleviating symptoms of diabetes mellitus. The purpose of the present study was to evaluate the activity of wungu leaf extracts in decreasing blood glucose level of alloxan (200 mg/kg BW)-induced hyperglycemic mice. Extracts of wungu leaf were obtained by macerating with ethanol and then partitioning the extract with diethyl ether, ethyl acetate, and butanol. Each extract obtained was used to treat hyperglycemic mice for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…G. pictum administered via the oral route effectively reduced blood glucose levels in alloxan-induced diabetes in mice at doses between 50 mg/kg and 200 mg/kg [ 54 ]. G. pictum extracts administered orally at 50 mg/kg over a period of 28 days were shown to decrease the glucose levels in blood by percentages ranging from 30 to 37% [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…G. pictum administered via the oral route effectively reduced blood glucose levels in alloxan-induced diabetes in mice at doses between 50 mg/kg and 200 mg/kg [ 54 ]. G. pictum extracts administered orally at 50 mg/kg over a period of 28 days were shown to decrease the glucose levels in blood by percentages ranging from 30 to 37% [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result revealed that all extracts decreased blood glucose level with a percentage of decrease ranging from 30 to 37% compared to glibenclamide (0.25 mg/kg) with a value of 56%. 19 Estrogenic effects 24 Oral treatment with hexane leaf extract of G. pictum (0.5 mg/0.05 ml olive oil) possessed an estrogenic effect by significantly increasing the diameter of the uterus, mucous layer thickness, lumen epithelial cell height, and glandular epithelial cell height compared to aquadesttreated group. However, the estrogenic effect of G. pictum remains significantly lower than Ethinyl estradiol as the positive control.…”
Section: Anti-diabetic Effectmentioning
confidence: 99%